Contemporary Pragmatics of the Epic Tale: Yakut Epos Olonkho - Semen S. Makarov (Studia Litterarum)
This paper explores the pragmatics of a traditional Siberian epic tale genre. The author analyzes this issue on the example of Yakut epos called Olonkho from the moment of its first records (mid-19 th century) up to the present. The first part of the paper reconstructs the information concerning the pragmatics of this genre in the non-written epoch on the basis of ethnographic notes, field materials, and “internal” data of the records of Yakut epic plots. The main focus is on the function of magic in the narratives. The ceremonial character of the performance, the recorded cases of its performance either during important festivities or, on the contrary, during community crises, the semantics of its plotlines allow us to consider the epos as a specific mode of magic influence on reality. The second part of the article features some facts that are relevant in terms of rethinking the status/functioning of the epic genre in the “post- traditional” era (e.g. the emergence of new forms of recording and circulation of the plots, attribution of epic tales to literary art, the inclusion of artistically elaborated epic texts in school curricula, overlaps between epic and popular song genres, etc.); it also describes the specificity of the perception of epic by contemporary representatives of Yakut tradition. The author points out at the emergence of such tendencies as institutionalization and codification of the narrative and dissemination of new ideas concerning the origins of the epic text. The described mode of transforming the traditional narrative genre into a marker of ethnic identity, aimed at the “other,” seems to be not specific for Yakut tradition only and thus may be extended to similar cases.